Early Exposure to Water Turbidity Affects Visual Capacities in Cuttlefish (Sepia officinalis) - Goerger, Alice; Darmaillacq, Anne-Sophie; Shashar, Nadav; Dickel, Ludovic (Frontiers in Physiology, 2021)
In La Manche (English Channel) the level of turbidity changes, not only seasonally and daily in seawater but also along the coast. As a consequence, vision in marine species is limited when based only on contrast-intensity. It is hypothesized that polarization sensitivity (PS) may help individuals detect preys and predators in turbid environments. In the cuttlefish, Sepia officinalis, to date, all behavioral studies have been conducted on animals reared in clear water. But the cuttlefish sensory system is adapted to a range of turbid environments. Our hypothesis was that rearing cuttlefish in clear water may affect the development of their visual system, and potentially affect their visually guided behaviors. To test this, newly-hatched cuttlefish, from eggs laid by females brought in from the wild, were reared for 1 month under three different conditions: clear water (C group), low turbidity (0.1 g / l of clay, 50–80 NTU, LT group) and high turbidity (0.5 g / l of clay, 300–400 NTU, HT group). The visual capacities of cuttlefish were tested with an optomotor apparatus at 7 days and at 1 month post-hatching. Optomotor responses of juveniles were measured by using three screen patterns (black and white stripes, linearly polarized stripes set at different orientations, and a uniform gray screen). Optomotor responses of juveniles suggest that exposure to turbid water improves the development of their PS when tested in clear water (especially in LT group) but not when tested in turbid water. We suggest that the use of slightly turbid water in rearing systems may improve the development of vision in young cuttlefish with no detrimental effect to their survival rate. Future research will consider water turbidity as a possible factor for the improvement of cuttlefish well-being in artificial rearing systems.